Mathematical methods for physics and engineering - Riley, K. F. (Kenneth Franklin), 1936-; Hobson, M. P. (Michael Paul), 1967-; Bence, S. J. (Stephen John), 1972- (Cambridge ; New York : Cambridge University Press, 2006)
The third edition of this highly acclaimed undergraduate textbook is suitable for teaching all the mathematics for an undergraduate course in any of the physical sciences. As well as lucid descriptions of all the topics and many worked examples, it contains over 800 exercises. New stand-alone chapters give a systematic account of the 'special functions' of physical science, cover an extended range of practical applications of complex variables, and give an introduction to quantum operators. Further tabulations, of relevance in statistics and numerical integration, have been added. In this edition, half of the exercises are provided with hints and answers and, in a separate manual available to both students and their teachers, complete worked solutions. The remaining exercises have no hints, answers or worked solutions and can be used for unaided homework; full solutions are available to instructors on a password-protected web site, www.cambridge.org/9780521679718.
Preliminary algebra Preliminary calculus Complex numbers and hyperbolic functions Series and limits Partial differentiation Multiple integrals Vector algebra Matrices and vector spaces Normal modes 10. Vector calculus Line, surface and volume integrals Fourier series Integral transforms First-order ordinary differential equations Higher ordinary differential equations Series solutions of ordinary differential equations Eigenfunction methods for differential equations Partial differential equations: general and particular Partial differential equations: separation of variables and other methods Complex variables Tensors Calculus of variations Integral equations Group theory Representation theory Probability Statistics Numerical methods Appendix Index Table of Contents provided by Publisher. All Rights Reserved.
Includes index.
Includes index.
1
Keywords: CIT; Mathematical analysis; Engineering mathematics; Mathematical physics